Autonomous navigation for mobility scooters: a complete framework based on open-source software - Cecotti, Marco; Kanchwala, Husain; Aouf, Nabil (IEEE, 2019)
In recent years, there has been a growing demand for small vehicles targeted at users with mobility restrictions and designed to operate on pedestrian areas. The users of these vehicles are generally required to be in control for the entire duration of their journey, but a lot more people could benefit from them if some of the driving tasks could be automated. In this scenario, we set out to develop an autonomous mobility scooter, with the aim to understand the commercial feasibility of a similar product. This paper reports on the progress of this project, proposing a framework for autonomous navigation on pedestrian areas, and focusing in particular on the construction of suitable costmaps. The proposed framework is based on open-source software, including a library created by the authors for the generation of costmaps.
Keywords: Three-dimensional displays; Motorcycles; Global navigation satellite system; Autonomous robots; Laser radar